"Trespassers are welcome" - Rennie, Elinor (Javnost (Ljubljana), 2003)
This article looks at the changing notion of access in communications policy. It compares the regime for community television access in Australia with new conceptions of access based on the notion of the information commons. Community television has been marginalised in broadcasting policy as it does not conform to the broadcasting regime of quid pro quo regulation whereby market stability is maintained in return for content requirements imposed uponthe commercial broadcasters. In the new media environment (in particular that of the narrowband Internet), access has begun to be conceived of as openness or "intercreativity," rather than as "access to" an otherwise controlled system. This article discusses how that change can contribute to the formation of new policy justifications for community broadcasting in the digital television environment. What is at stake is a shift from seeing community media as oppositional and marginal to new notions of community-based media that are empowering and generative in nature.
Keywords: družbene skupine; lokalne skupnosti; interesi; komuniciranje; communication; informiranje; mass media; množični mediji; television; televizija; digital television; digitalna televizija; medijska politika